Advanced cardiovascular monitoring. Issue 2 (February 2016) - Shaw, Michelle; Chishti, Ahmed
Abstract: Advanced cardiovascular monitoring has a role in the assessment and management of both haemodynamically unstable critically ill and high-risk perioperative patients. Clinical indicators and standard monitoring may be unreliable or insufficient in these patients. This article reviews basic cardiovascular physiology, goal directed haemodynamic therapy and advanced cardiovascular monitoring with evidence and recommendations. Specific monitoring modalities will be described including invasive pressure monitoring, arterial waveform analysis and cardiac output estimation by dilutional, Doppler and echocardiography methods. Emerging technologies will also be discussed.